PELAYANAN FISIOTERAPI PADA SPRAIN ANKLE DI DESA JATIPURO KECAMATAN TRUCUK KABUPATEN KLATEN - Amalia, Amalia Solichati Rizqi; Wanito Ambarsari, Dwi; Wahyu putra, Yudha; Suwarni, Sri (LPPM Universitas Widya Dharma Klaten, 2023)
Introduction physical activities carried out by residents resulted in several residents experiencing injuries, one of which was an ankle sprain injury. The method of activities carried out to help solve problems is the method of free physiotherapy services, especially in the case of an ankle sprain which was carried out at the elderly Posyandu in Jatipuro Village, Trucuk District, Klaten Regency on Saturday 11 June 2022. The purpose of this service is to improve health in the community The results of physiotherapy services are carried out with a physiotherapy process, namely history, diagnosis, intervention, and evaluation. Conclusion community service can run smoothly and the participants are so enthusiastic about paying attention and doing free therapy